A STUDY ON TRANEXAMIC ACID ROLE FOR SEROMA REDUCTION IN VENTRAL HERNIA REPAIR - JUNAID, A; ALI, MH; MUZZAMIL, K; HAQ, IU; JAVED, MA; HUSSIAN, Z (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to investigate whether tranexamic acid is effective in reducing seroma formation after ventral hernia repair. The study was conducted at multiple centers, including the Department of Surgery at Khyber Teaching Hospital Peshawar and Hayatabad Medical Complex, Peshawar, from January 2023 to June 2023. The study included 70 patients of either gender, aged 18 to 50 years, undergoing ventral hernia repair. After the administration of tranexamic acid, the formation of postoperative seroma was studied. The study found that 35.7% of the patients were male, while 64.3% were female. In 53 (75.71%) patients, seroma formation subsided within six days, while in 17 (24.28%) patients, it took more than six days for seroma formation to subside (P = 0.0001).In conclusion, the study showed that tranexamic acid significantly reduced postoperative seroma formation in patients after ventral hernia repair.